(untitled) (Research, Society and Development, 2021)
Objective: To describe the nosological profile of maternal mortality in the Health Region of Marajó II / PA, from 2010 to 2019. Methods: Epidemiological, descriptive, retrospective study, using secondary data from DATASUS, linked to maternal death records, considering the variables: type of delivery, basic cause and time of death, parity and number of prenatal consultations of the mother, in addition to age, marital status, education and occupation at delivery (death situation). Results: No evaluated period in Pará was recorded in 1,061 maternal deaths, representing the ratio of maternal mortality to 113.76 deaths / 100 thousand live births. Of all registered deaths, 71 occurred in Marajó II (98.97 deaths per 100,000 live births). Mortality the main groups, classified by codes of chapter XV of the ICD-10, were: Eclampsia (O15) and Placental abruption (O45). Most of the negative events occurred among young, single pregnant women, with low educational level and without paid activities. Conclusion: The maternal mortality ratio is above acceptable parameters and affects mainly women in situations of high vulnerability. This highlights the need to adopt a new model of health care for women capable of organizing a care network meeting the needs of groups that are economically and socially disadvantaged.